O emprego e a sobre-educaç\~ao de doutores no setor privado brasileiro no período 2010-2021 - Daniel Gama e Colombo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This article aims to investigate the evolution of the employment of Ph.D. holders in the Brazilian private sector between 2010 and 2021. The study is based on microdata on formal employment from the Annual Social Information Report (Rais), and it presents descriptive statistics regarding employment, remuneration, and over-education of PhDs. Over-education is measured using the realized matches method and, additionally, the job analysis approach. The results suggest that, throughout the period of analysis, there was an increase in the number of Ph.D.s employed and a reduction in the average compensation. Furthermore, there was an increase in the rate of overeducation among professionals with a doctorate degree, and the average monthly compensation and hourly wages in 2021 were higher for those in occupations that matched their educational level.
Keywords: I23; I26; J24; 330; compensation; educational alignment; overeducation; PhD